An experimental study on stress-dependent sensitivity of ultra-low permeability sandstone reservoirs - Xie, Sam; Jiao, C.; He, S.; Xie, Q.; Gu, D.; Zhu, H.; Sun L; Liu, H. (2011)
According to the theory of dual effective stress, the present paper studied the stress-dependent sensitivity of ultra-low permeability sandstone cores(full diameter) sampled from the Triassic outcrop of the Ordos Basin by using an automatic core displacement system. The experimental results indicated that when the method with variable internal pressure but constant peripheral pressure was used, the outcome went against common knowledge due to the zero drift of both the pressure sensor and the differential pressure sensor caused by broad variations in fluid pressure. So the method with constant internal pressure but variable peripheral pressure was adopted in the test, and the outcome demonstrated that the process of rock deformation could be divided into two phases, namely the microcrack closure phase and the rock compression phase. During the first phase, the permeability reduced dramatically by 20% due to the closure of microcracks, while in the second phase, the permeability decreased slowly by 5% with the increase of peripheral pressure that keeps compressing rocks. Therefore, the paper proposed that the stress-dependent sensitivity of ultra-low permeability reservoirs under the in-situ stress was weak and its effect on the productivity of low permeability reservoirs was negligible.